Estratégias enunciativas na formação de territórios: memórias discursivas, narrativas de vida e escrevivências em Conceição Evaristo e Grada Kilomba - Rodrigo Pires Paula (2024)
The research that led me to write this thesis aims to address some concepts linked to negrocontradiaspórico geographic and discursive spaces and territórios, based on life narratives expressed by two writers of black origin. We take into account the conflicts that appear between center and periphery, based on mental and discursive memories (individual and collective) of the characters who go through these narratives. A discussion was promoted about the differences and theoretical similarities between autobiographical pact, autofiction, life narratives and a writing called escrevivência, by the Brazilian author Conceição Evaristo. Thus, we present forms of colonial violence, in which we identify cultural models, stereotypes, etc., which gave rise to other concepts contrary to the work of the African diaspora. The Brazilian neologism escrevivências takes into account both psychic memories and memories translated by written speech and were extracted from the writer's individual and collective of people of African origin who are victims of the diaspora, like her and Grada Kilomba, the other writer who is part of the thesis corpus, among many other characters displaced against their will from Africa. The methodology used in the research is the result of an exploratory study of several bibliographic sources, in a specific interdisciplinary movement of Semiolinguistic, the Discourse Analysis current on which the work is based.